2012
DOI: 10.1002/zaac.201200171
|View full text |Cite
|
Sign up to set email alerts
|

Na3B3O3F6: Synthesis, Crystal Structure, and Ionic Conductivity

Abstract: Crystalline Na 3 B 3 O 3 F 6 was synthesized from H 3 BO 3 and NaBF 4 at 623 K, alternatively NaBO 2 can be reacted with NaBF 4 at 673 K. The title compound (C2/c, a = 11.866 (7), b = 6.901(4), c = 9.367(6) Å, β = 113.724(9)°) contains the cyclo-fluorooxotriborate anion B 3 O 3 F 6 3-, which displays a planar B 3 O 3 ring. Within the margins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
3
26
0
1
Order By: Relevance
“…The FBB of K 3 B 6 O 9 F 3 is the [B 6 O 11 F 3 ] 7− unit, which can be described as an interconnection of the [B 3 O 5 ] − boroxine, [B 3 O 5 F] 2− fluorinated boroxine rings, and [BO 2 F 2 ] 3− tetrahedron at a ratio of 1:1:1. The [B 3 O 5 ] − boroxine is a near‐planar ring, whereas the fluorinated boroxine [B 3 O 5 F] 2− ring exhibits a twisted boat conformation with the maximum torsion angle B2‐O4‐B5‐O3=31.38°, which is comparable with those of the fluorinated boroxine rings in LiB 6 O 9 F, Li 2 B 3 O 4 F 3 , Na 3 B 3 O 3 F 6 , NH 4 B 4 O 6 F, and BiB 2 O 4 F . Each FBB is connected with four neighboring FBBs, by sharing the O6 and O7 atoms, forming a unique two‐dimensional zigzag infinite 0pt2.84526pt22.84526pt [B 6 O 9 F 3 ] 3− layer.…”
Section: Figurementioning
confidence: 92%
“…The FBB of K 3 B 6 O 9 F 3 is the [B 6 O 11 F 3 ] 7− unit, which can be described as an interconnection of the [B 3 O 5 ] − boroxine, [B 3 O 5 F] 2− fluorinated boroxine rings, and [BO 2 F 2 ] 3− tetrahedron at a ratio of 1:1:1. The [B 3 O 5 ] − boroxine is a near‐planar ring, whereas the fluorinated boroxine [B 3 O 5 F] 2− ring exhibits a twisted boat conformation with the maximum torsion angle B2‐O4‐B5‐O3=31.38°, which is comparable with those of the fluorinated boroxine rings in LiB 6 O 9 F, Li 2 B 3 O 4 F 3 , Na 3 B 3 O 3 F 6 , NH 4 B 4 O 6 F, and BiB 2 O 4 F . Each FBB is connected with four neighboring FBBs, by sharing the O6 and O7 atoms, forming a unique two‐dimensional zigzag infinite 0pt2.84526pt22.84526pt [B 6 O 9 F 3 ] 3− layer.…”
Section: Figurementioning
confidence: 92%
“…For instance, borates also allow forat rigonal planar coordination of the network buildingc ation boron. The inorganic fluorooxoborates known so far comprise trivalent bismuth [6,7] and mainly alkali metal as well as ammonium cations, [8][9][10][11][12][13][14][15][16][17][18][19][20] which were investigated with regard to their behaviour as ionicc onductors or their nonlinear opticalproperties.…”
Section: Introductionmentioning
confidence: 99%
“…Jansen et al. developed several inorganic fluorooxoborates as solid ionic conductors, such as LiB 6 O 9 F, Li 2 B 6 O 9 F 2 , Li 2 B 3 O 4 F 3 , and Na 3 B 3 O 3 F 6 . The electronic and optical properties of three lithium fluorooxoborates were also studied both theoretically and experimentally .…”
Section: The Characteristics Of Fluorooxoboratesmentioning
confidence: 99%
“…[130,131] [111] and Na 3 B 3 O 3 F 6 . [112] The electronic and opticalp roperties of three lithium fluorooxoborates werea lso studied both theoretically and experimentally. [141,142] After this, we re-investigated the three acentric lithium fluorooxoboratesb yt he density functional theory (DFT) method and found that Li 2 B 6 O 9 F 2 is an outstanding DUV NLO crystal without debilitating layering.…”
Section: The Characteristics Of Fluorooxoboratesmentioning
confidence: 99%